2020
DOI: 10.1016/j.heliyon.2020.e04157
|View full text |Cite
|
Sign up to set email alerts
|

Physical and mechanical properties of Entada mannii particulates reinforced composites

Abstract: This paper reports the physical and mechanical properties of Entada mannii particulates reinforced composites. Polypropylene (PP) based composites filled with Entada mannii ash particulates was produced using the compression moulding. The thermal properties, structural characteristic and morphology of the composites and ash particulate were studied. Tensile properties, impact strength and flexural properties were used to evaluate the mechanical behaviour of composites. Tensile properties, elastic modulus and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
1
2
0
Order By: Relevance
“…Also, groundnut husk particulate infusion in polyethylene by Azeez et al 66 revealed consecutive improvement in hardness as filler proportion increased from 5 to 35% (at 5% interval). Same feat was observed in the findings of Hassan et al 65 ; Ahmed et al 67 ; Balogun et al 68 . The achievement is associated with the hardness of particles owing to the silica and alumina content (Table 1).…”
Section: Methodssupporting
confidence: 81%
“…Also, groundnut husk particulate infusion in polyethylene by Azeez et al 66 revealed consecutive improvement in hardness as filler proportion increased from 5 to 35% (at 5% interval). Same feat was observed in the findings of Hassan et al 65 ; Ahmed et al 67 ; Balogun et al 68 . The achievement is associated with the hardness of particles owing to the silica and alumina content (Table 1).…”
Section: Methodssupporting
confidence: 81%
“…However, Entada mannii plant is a liana plant and climber that entangles the trunk on their host. The plant stem is structured with arrangements of fiber bundles within the bark stem [22]. The fibers are twined around the bark stem, which enhanced the bending and torsional strength for the plant system.…”
Section: Introductionmentioning
confidence: 99%
“…A review by Yekinni et al [18] reported that fine particles of SiC, Al2O3, graphene and aluminide are harder reinforcements materials and therefore have the capacity to improve the hardness and strength of metal matrix composites. This improvement could be credited to good reinforcement particles wettability within the matrix which enhances the adhesion between reinforcements and the matrix, thus impeding the movement of the crack propagation on the application of a pulling load [27]. The reinforcement particles penetrates into the matrix interphase and displaces gas bubbles from being trapped within the AA6063 matrix.…”
Section: Figure 1 Percentage Porosity Of the Developed Hybrid Compositesmentioning
confidence: 99%